The Role of Different Diets in Shaping the Gut Microbiome - Opoka, Paulina; Bojarzyńska, Gracja; Pawul, Weronika; Woźnica, Weronika; Ćwiek, Zuzanna; Mińkowska, Aleksandra; Lucima, Łukasz; Barański, Michał; Wydra, Klaudia; Kondracka, Monika (Journal of Education, Health and Sport, 2025)
Introduction and Objective The gut microbiota plays a crucial role in metabolism, immunity, and digestion, with diet being a key factor shaping its composition. Disruptions in microbiota balance contribute to chronic diseases like obesity and insulin resistance. This study examines the impact of various dietary patterns—Mediterranean, ketogenic, high-protein, gluten-free, and low FODMAP diets—on gut microbiota, highlighting their mechanisms, benefits, and risks to metabolic health. Review Methods A literature review of peer-reviewed studies on diet-microbiota interactions was conducted, focusing on microbiota composition, function, and metabolic effects. Abbreviated Description of the State of Knowledge The Mediterranean diet enhances beneficial bacteria, increases short-chain fatty acid (SCFA) production, and reduces inflammation, improving gut barrier integrity. The ketogenic diet alters microbiota by decreasing carbohydrate-fermenting bacteria, with both positive and negative metabolic outcomes. The low FODMAP diet alleviates irritable bowel syndrome symptoms but may reduce beneficial bacteria like Bifidobacterium. A high-protein diet increases bacteria involved in amino acid metabolism, yielding mixed effects on metabolic health. The gluten-free diet, while essential for celiac patients, may reduce microbiota diversity and lead to nutrient deficiencies. Each diet uniquely influences gut microbiota, underscoring the need for tailored dietary strategies to support metabolic and overall health. Summary Diet significantly impacts gut microbiota composition and function, affecting metabolic and immune health. Maintaining microbiota balance is crucial for homeostasis, as dysbiosis can contribute to disease. Understanding diet-microbiome interactions is essential for developing evidence-based nutritional strategies to optimize health.